Cone‐beam computed tomography evaluation of C-shaped root and canal morphology of mandibular premolars - Gisbeli Brea; Francisco Gomez; Jose Francisco Gomez-Sosa (BMC, 2021)
Abstract Background Mandibular premolars are complicated teeth to endodontically treat due to the anatomical variations that can present. The purpose of this study was to determine the presence of C-shaped configurations in mandibular premolars by cone-beam computed tomography (CBCT). Methods 380 mandibular first premolars and 308 mandibular second premolars cone-beam computed tomographic images were obtained from 292 patients (175 female and 117 male). Tooth position, number of roots, root canals, C-shaped root canal system configuration, level of canal bifurcation and radicular grooves were evaluated by two endodontists trained in CBCT evaluation; previously calibrated between them, and a radiologist with endodontic experience. Data were statistically compared by The Chi-square test (α = 0.05) to examine any significant difference between gender and C-shaped root canal system and any significant difference between C-shaped configuration according to Fan criteria and gender. Results Overall 100% (n = 688) teeth examined, 19.2% (n = 132) had a C-shaped root canals system. 9.16% (n = 63) in male patients and 10.03% (n = 69) in female patients. The prevalence of C-shaped root canal system in mandibular first premolar was 83.33 and 16.66% in mandibular second premolars. According to Fan classification, the mandibular first premolars showed 3.63% as C1, 9.09% C2, 59.09% C3, 21.81% C4a, 1.8% C4b. Mandibular second premolars showed 13.63% as C1, 18.18% C2, 13.63% C3, 27.27% C4a, 9.09% C4b. Male patients showed 4.54% as C1, 3.78% C2, 22.72% C3, 11.36% C4a, 0.75% C4b, and 4.54% out of classification. Female patients showed 0.75% as C1, 6.81% C2, 30.03% C3, 9.84 C4a, 2.27% C4b, and 2.27% out of classification. The 53.36% canal bifurcation in mandibular first premolars and 50.09% in mandibular second premolars were in the middle third. No statistical differences were found between C-shaped root canal system and gender or C-shaped configuration according to Fan criteria and gender. P was < 0.05. Conclusions Within the limitation of this study, the presence of C-shaped anatomical system is relatively low in mandibular second premolars than in mandibular first premolars.